Assessment of infectious diseases in commercial frozen semen straws of water buffalo bulls. Preliminary results - Rosaura Pérez-Gil (Revista Científica)
Different infectious diseases in water buffaloes may be disseminated through semen, such as Leptospira spp. The objective of this investigation was to determine the presence of antibodies against the Infectious Bovine Rhinotracheitis (IBR), Bovine Viral Diarrhea Virus (BVDV) and Neospora caninum, as well as the contamination with Leptospira spp. in frozen semen from water buffalo bulls (Bubalus bubalis). For this, 14 straws from seven farms in the states of Barinas (farm C and D), Cojedes (farm A, F and G), Mérida (farm B) and Zulia (farm E), Venezuela, were evaluated. The animals from farms A, B, C, E and F were vaccinated against IBR and BVDV; farms D, and G did not vaccinate against these diseases. The detection of antibodies against the gB glycoprotein of the IBR virus and the p80 protein of the BVDV and against Neospora caninum was performed using the ELISA technique according to the detection kit manufacturer IDvet and IDEXX specifications. In addition, semen was cultured in Ellinghausen McCullough, Johnson and Harris medium (EMJH), which is selective to isolate Leptospira spp. The presence of antibodies against IBR was detected in 28,6% of the straws evaluated (farm: A 1/2; D 1/1; F 1/3 and G 1/2); however, on farm A and F the animals were vaccinated 180 days before semen collection and the antibodies detected could come from the secretion of the accessory glands (seminal plasma); the antibodies detected in straws from farms D and G are attributed to an active infection of the IBR virus and are the product of a systemic response of the animal. In the case of BVDV and Neospora caninum, 100% of the straws were negative. In the culture for the isolation of Leptospira spp, 50% of the straws were positive (farm: A 2/2; D 1/1; E 2/2 and G 2/2). Leptospira infection in males is often subclinical, and the bacteria can remain in the seminal vesicles, increasing the chances of spreading. In conclusion, the use of straws without due prior disease control represents a significant risk factor in their spread, which is why these results demonstrate the need for screening for IBR, BVDV, Neospora caninum, Leptospira spp., and other diseases in water buffalo bulls destined for commercial freezing of semen to reduce the risk of spreading venereal diseases. It is recommended to comply with the indications of the Terrestrial Animal Health Code (Chapter 4.7) from the World Organization for Animal Health (WOAH) and include other pathologies established in this code and that were not contemplated in this study.